2021
DOI: 10.18632/aging.203360
|View full text |Cite
|
Sign up to set email alerts
|

A combined hypoxia and immune gene signature for predicting survival and risk stratification in triple-negative breast cancer

Abstract: Background: Increasing evidence showed that the clinical significance of the interaction between hypoxia and immune status in tumor microenvironment. However, reliable biomarkers based on the hypoxia and immune status in triple-negative breast cancer (TNBC) have not been well established. This study aimed to explore a gene signature based on the hypoxia and immune status for predicting prognosis, risk stratification, and individual treatment in TNBC. Methods: Hypoxia-related genes (HRGs) and Immune-related gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Our present work identified that hypoxia-related genes and the risk score model built on them were significantly correlated with the prognosis of CC patients. Similar results were found in ovarian cancer ( Chen et al, 2021 ), triple-negative breast cancer ( Yang et al, 2021a ), osteosarcoma in children ( Jiang et al, 2021a ), acute myeloid leukemia ( Jiang et al, 2021b ), and so on. It indicated that along with other factors, hypoxia might play an important role in the development and progression of cancer.…”
Section: Discussionsupporting
confidence: 75%
“…Our present work identified that hypoxia-related genes and the risk score model built on them were significantly correlated with the prognosis of CC patients. Similar results were found in ovarian cancer ( Chen et al, 2021 ), triple-negative breast cancer ( Yang et al, 2021a ), osteosarcoma in children ( Jiang et al, 2021a ), acute myeloid leukemia ( Jiang et al, 2021b ), and so on. It indicated that along with other factors, hypoxia might play an important role in the development and progression of cancer.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies also identified that hypoxia could induce the high expression of immune checkpoint molecules, such as indoleamine 2,3-dioxygenase (IDO) and PD-L1 [ 50 , 51 ]. The expression of immune checkpoint molecules might be negatively associated with the infiltration of TILs and the prognosis in types of cancers [ 7 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Z-score method was used to standardize the ssGSEA scores and risk scores [ 18 ]. The Kaplan–Meier method was used to perform survival analysis.…”
Section: Methodsmentioning
confidence: 99%